Good people - Genz, Henrik Ruben, 1959-; Franco, James, 1978-; Hudson, Kate, 1979-; Wilkinson, Tom, 1948-2023; Sy, Omar, 1978-; Friel, Anna, 1976-; Sakey, Marcus; Eyeworks Fine & Mellow (Firm); Material Pictures; Film 360 (Firm); Millennium Films; Millennium Entertainment, LLC. ([Place of publication not identified] : [Publisher not identified], 2014)
A young American couple falls into severe debt while renovating a home in London. When they discover that the tenant in the apartment below them was murdered and left $400,000 cash stashed in the ceiling, the couple thinks all of their problems are solved, but that's when very bad things start happening to good people.
Based on the novel "Good People".
Music by Neil Davidge; editor, Paul Tothill; director of photography, Jorgen Johansson.
James Franco, Kate Hudson, Tom Wilkinson, Omar Sy, Sam Spruell, Anna Friel, Thomas Arnold, Oliver Dimsdale, Diana Hardcastle, Michael Jibson, Diarmaid Murtag.
MPAA rating: R; for bloody violence and language.
DVD, 16 x 9 presentation; region 1; Dolby Digital 5.1.
English dialogue; Spanish subtitles; English subtitles for the deaf and hard of hearing.
Keywords: Murder -- Drama; Debt -- Drama; London (England) -- Drama; Action and adventure films; Video recordings for the hearing impaired; Thriller films; Feature films